The Analysis of Gender Position in English Language Teaching Coursebooks: Pathway to English for The Senior High School - Afifah Nur Amalia; Didin Nuruddin Hidayat; Nida Husna; Alek Alek (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The gender status in ELT (English Language Teaching) textbooks for Eleventh Grade Students is examined in this study. The study goals are as follows: to determine what gender position is equal in the textbook Pathway to English and to identify what male and female roles are appropriate for their gender position in the textbook. Content analysis was employed as the study approach. The data from this study were studied in six areas of gender, and they are: Female or male graphical depiction or illustration, female and male characters who play professional/occupational roles, proper nouns, pronouns, common nouns, and titles are all stated as female or male. Female and male role models: The number of role models, female/male activities are any actions performed by a female or a man. The pattern of mentioning female/male names refers to female and male characters in the same sentence. The data shows that the numerical representation of females in this book is less than males in all aspects.